From Lowest Unit Price to Lowest Total Supply Risk: A System Shift Framework for Resilience in the Global Generic Pharmaceutical Industry - Raymond R. Tjandrawinata (Journal of World Science, 2026)
Generic medicines are routinely framed as a success of price competition, yet recent evidence suggests that the same competitive architecture which lowers unit prices may also weaken supply resilience. Drug shortages, approved-but-unlaunched generics, geographically concentrated active pharmaceutical ingredient (API) production, sterile-injectable vulnerabilities, and the rising technical complexity of biosimilars indicate that the global generic pharmaceutical industry is undergoing a deeper system transition. This article developed a System Shift framework to analyse these structural challenges, linking seven analytical factors: system condition, domain lock, actors, chokepoints, position, strategy, and feedback. Using a public-source qualitative comparative case analysis of twenty companies across global, Indian, European, North American, Chinese, Korean, South African, and Southeast Asian contexts, the paper identifies recurring patterns of vulnerability and strategic adaptation. The analysis shows that generic firms are not a homogeneous low-margin group; they include global off-patent platforms, vertically integrated Indian exporters, sterile-injectable specialists, biosimilar platforms, regional branded-generic leaders, and national manufacturers. Across these archetypes, the dominant feedback signal remains lowest unit price, while quality maturity, supplier redundancy, and launch reliability remain weakly rewarded. The central conclusion is that generic pharmaceutical governance must shift from a cheapest-unit paradigm toward a lowest-total-supply-risk paradigm. Procurement, regulation, and corporate strategy must incorporate multi-award tendering, explicit supply-security criteria, accelerated regulatory variation pathways, resilient API sourcing, and transparent shortage-prevention feedback loops. The paper contributes a conceptual and policy framework for reinterpreting generic medicines as resilience infrastructure rather than merely low-cost therapeutic substitutes.